If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = -1d + 20 Reorder the terms: 15 = 20 + -1d Solving 15 = 20 + -1d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add 'd' to each side of the equation. 15 + d = 20 + -1d + d Combine like terms: -1d + d = 0 15 + d = 20 + 0 15 + d = 20 Add '-15' to each side of the equation. 15 + -15 + d = 20 + -15 Combine like terms: 15 + -15 = 0 0 + d = 20 + -15 d = 20 + -15 Combine like terms: 20 + -15 = 5 d = 5 Simplifying d = 5
| y(y+8)= | | 8n+1-6n+5=-4(-6-3n)-8(-1+n) | | -98k=7+4k | | 5n-25+4=8n+3 | | 5+3r=5r+12 | | -6y-3=3-3y | | 2=35x-13 | | 19x+26=121 | | 4t-6=5(t+5) | | 19x+26=21 | | 4n-12=13-4n | | 13x-2(3x+6)= | | -8n+12=-4n-4 | | 2n^2+11n+10=0 | | r^2-8r-20=0 | | 7-7=18x+8x | | 3(x+8)=3x+12 | | x/2=-30+35 | | 3x+4x^2=56 | | -4+10=12x-5-11x | | 3(v-2)-5v=-2(v+2) | | 3(2x-5)=7(x+2) | | v^2+6v-7= | | -6(u+1)+8u=2(u-3) | | 5x+9x+2+x= | | -4+15=14-2-13x | | -3x=57 | | 2(x+2)=7x+4 | | -2v^2+8v+24= | | 6x^2-14x^2=0 | | (8x+12)=(5x+57) | | 4x+2(x+65)=36 |